Online Food Delivery Platforms and Female Labor Force Participation - Liu, Jialu; Pei, Siqi; Zhang, Xiaoquan (Michael) (Information Systems Research, 2024)
Our research examines the impact of online food delivery platforms on female employment in South Korea, highlighting the often-overlooked positive externalities that digital platforms generate on the labor market and economics. We find that these platforms lead to an immediate and lasting increase in the female employment rate, with a notable increase in the female employment rate by 6.5%. The economic benefits derived from this rise in female employment account for 0.27% to the country’s GDP, or 17 times the revenue of the online food delivery platform. Our analysis shows that such digital platforms offer a pathway for women to break free from traditional household roles, thus granting them more time and the opportunity to decide whether to join the labor market or stay at home. The freedom to be able to join the labor force promotes gender equality and fosters economic engagement. Policymakers need to recognize such indirect effects of technology-driven business models because they shape labor markets and drive economic outcomes. This research has vital implications for practice and policy, offering fresh perspectives on fostering female labor force participation and boosting economic growth. Empowering individual households and granting women greater agency can have profound effects, supplementing organizational measures. The study highlights the underestimated economic and societal value created by innovative technology platforms, emphasizing the need for policymakers to consider these spillover effects when assessing and regulating such platforms. Leveraging digital platforms can lead countries toward a more inclusive and prosperous future, dismantling barriers and promoting gender equality.